Virulence distribution and variability in Erysiphe graminis tritici - and R. AGGARWAL, P. BAHADUR, C.P. KHARE (Indian Phytopathology, 2002)
Virulence analysis of powdery mildew of wheat from Haryana, Himachal Pradesh, Uttar Pradesh and Tamil Nadu (Nilgiris) on 10 Pm lines-Pm 2, Pm 3a, Pm 3b, Pm 4, Pm 5, Pm 6, Pm 7, Pm 8 and Pm Ma revealed the existence of 26 pathotypes. Four pathotypes were common in North-western India and Nilgiris (Tamil adu). Races 5 and 17 identified by Sharma and Singh (1990) tallied with avirulence/virulence combinations Pm 2, 3b, 3c, 4, 6, 7, 81Pm 3a, Ma and Pm 2, 3a, 4, 6, 81 Pm 3b, 3c, Ma identified from Himachal Pradesh. Increase in virulence on Pm 8 in orth-western India may be due to cultivation of wheat varieties derived from 'Veery'.